A review of college-level health textbooks for coverage of type 2 diabetes, prediabetes, and metabolic syndrome. (March 2014) - Ethan, Danna; Rennis, Lesley; Samuel, Lalitha; Seidel, Erica J; Basch, Corey H
Objective: Type 2 diabetes, prediabetes, and metabolic syndrome are increasingly relevant health problems for United States (US) college-aged students and their family members. This study's aim was to determine the extent to which these chronic conditions were covered in leading college-level personal health textbooks and to what degree the books emphasized the preventive steps students can take to promote their health and minimize development or worsening of these conditions. Design: A convenience sample of 10 leading college-level personal health textbooks was used in this cross-sectional study. Setting: Textbooks selected for analysis are frequently used in introductory personal health courses on college campuses across the US. Method: Textbooks were coded for level of coverage for select criteria that included risk factors, definitions, prevalence among college-aged youth, African Americans, and Hispanics, serious consequences associated with unmanaged type 2 diabetes, presence of self-assessment tool, prediabetes' and metabolic syndrome's association with type 2 diabetes, prevention strategies, student portrayals, and messages geared towards students living with these conditions. Results: Exemplary coverage of information related to diabetes, prediabetes, and metabolic syndrome was uncommon for the following criteria: prevalence among African Americans and Hispanics, depiction of a student with diabetes or prediabetes, prevalence of messages geared toward readers with these conditions, and in-depth discussion of prevention strategies. Conclusion: More thorough coverage in personal health textbooks is necessary given the rising prevalence of these health problems in young adults, the positive impact of healthy lifestyle choices, and the formal opportunity for learning presented through college personal health courses.